Range of motion on increasing muscle strength in the elderly - Sujatmiko (Nursing and Health Sciences Journal (NHSJ), 2025)
Decreased muscle strength in the elderly often causes a decrease in quality of life and mobility. One intervention that can be done to increase muscle strength is active Range of Motion (ROM) training. This study aims to determine the effect of active ROM training on increasing muscle strength in the elderly at the UPT Social Services for the Elderly in Jombang. This research used a pre-experimental design with a one-group pretest-posttest approach. The research sample consisted of 36 older adults selected using purposive sampling. Data was collected by measuring muscle strength before and after active ROM exercises for four weeks. Data were analyzed using the Wilcoxon Signed-Rank Test statistical test with a significance level of α = 0.05. Before active ROM training, most respondents had level 3 muscle strength (61%). After active ROM training, most respondents experienced increased muscle strength to level 5 (75%). The statistical analysis results show a value of ρ = 0.000 ≤ 0.05, which shows a significant influence of active ROM training on increasing muscle strength in the elderly. Active ROM training is effective in increasing muscle strength in the elderly. Therefore, this exercise can be recommended as a routine program to maintain the physical health and mobility of the elderly. Further research with experimental designs and larger sample sizes is recommended to strengthen these findings.